Analysis of Scheme Types in the Focus of the Lecturer's Research Area Based on Tri Hita Karana Philosophy - Sudiana, I Ketut; I Made Sugiarta; Nia Erlina (Jurnal Pendidikan Indonesia, 2024)
Ganesha University of Education has a vision to become a superior university based on the Tri Hita Karana philosophy in Asia by 2045. This study analyzes the types of Undiksha academic research schemes throughout 2022, focusing on seven research areas. The type of research conducted is ex-post facto with a meta-analysis method that combines various research data from the Undiksha academic community throughout 2022 and then summarized quantitatively. The subjects of this study were all lecturers and functional staff of Undiksha. Factual data on the publication of lecturers' research results were obtained through documentation, questionnaires, interviews, and FGDs. The study results show that all research focus areas planned in the Undiksha Renstra for 2022-2026 have been filled, with research dominating in education, social humanities, and arts and culture as Undiksha's leading focuses. This research is an evaluation research with a qualitative research type. This study applies a goal-oriented evaluation model carried out in three stages: formulating goals, classifying goals, measurably formulating goals, determining when goal achievement can be demonstrated, selecting and developing appropriate measurement methods, collecting information or data, and analogizing data or information objectively. This study's implications can enrich the scientific treasury on how local philosophy, such as Tri Hita Karana, which emphasizes the harmony of human relations with God, fellow humans, and nature, can be the basis for determining research schemes.